Fabrication and Investigating the Electrical and Optical Properties of Silver Nanowire/Indium Tin Oxide Transparent Conductive Electrodes - Tran, Quoc Hoan; Chu, Duc Thanh; Hoang, Van Hoan; Nguyen, Dang Tuyen; Nguyen, Duy Cuong (JST: Engineering And Technology For Sustainable Development, 2021)
In this study, we analyze the optical and electrical properties of silver nanowires/indium tin oxide (AgNWs/ITO) transparent conductive electrodes (TCEs). AgNWs was synthesized by polyol method. ITO was deposited by direct-current sputtering. The diameter and length of the synthesized AgNWs are in the range of 40–70 nm and 5–30 µm, respectively. The AgNW TCEs have a rather high resistance (~210 Ω/□). After a layer of ITO sputtered on AgNW TCE, the resistance dropped sharply (~30.1 Ω/□) corresponding to 84.1% transmittance at 550 nm. The figure of merit of this TCE is 68.3. This result shows that the fabricated AgNWs/ITO TCEs have great potential in application as window electrodes for solar cells and LED devices.